Lebanon's perilous balancing act - Fakhoury, Tamirace (2015)
Comprised of eighteen officially recognized ethno-sectarian communities, Lebanon is a striking example of a state that is deeply divided yet has a consensus-oriented government. While the ripple effects of the Arab Spring have spread throughout the region, Lebanon has remained relatively calm. In contrast with neighboring countries, the level of state repression has remained low. Conflicting interests and struggles over the spoils of power have weakened governance structures, enabling outside conflict to seep into Lebanon. While the Arab protest wave stirred polarizing discourses in Lebanon, the war in Syria has had far more severe effects on its small neighbor. The aims of this approach would be to loosen the elite's grip on economic and political power, strengthen governing institutions, and bolster social cohesion. In a region shaken by state erosion and sectarian violence, the fragile Lebanese polity must rise to the task of effective governance. It can do so only if its gatekeepers implement the politics of power sharing in a more inclusive way.